al-Akhtha' as-Sya'i'ah Fi Istai'mal al-Lughah al-'Arabiyah Bi Indonesia - Yenni Patriani (Arabiyatuna: Jurnal Bahasa Arab, 2017)
The importance of Arabic is also reflected in the fact that it is the key to Islamic and Arab culture, As it allows the learner to see how much civilized and intellectual nation has been raised on the throne of the world for several centuries, And left a great cultural legacy in various arts and various sciences. There have been many mistakes in the use of the Arabic language in Indonesia, countless. And the most important reasons that led to the prevalence of this disturbing number of errors in the language of Hadad, the language of the last messages of God - the Almighty - the status of the Seal of the prophets and messengers to inform the worshipers of God.